Consumption habits and preferences by type of drink coffee (Coffea arabica L.) between young people from Machado / MG - Prado, Agda Silva; Paiva, Elisângela Furtado; Pereira, Rosemary Gualberto; Sette, Ricardo Souza; Silva, Jack Robson; Paiva, Leandro Carlos; Barbosa, Cleber Ávila (Coffee Science - ISSN 1984-3909, 2011)
The objective of this work was to identify the patterns of consumption and preference between different types of coffee (strictly soft, soft, hard, Riada and rio) among students in the city of Machado / MG. The research was conclusive descriptive, of a quantitative nature, to analyze the habits of the people interviewed through questionnaires. To identify a preference among the five types of drink provided, each one was coded and served, and the respondent chose the most preferred and noted it in the questionnaire. The method was carried out through individual interviews. The type of sampling was a randomized control trial and the individual questionnaires were tabulated and analyzed by SPSS software. It was concluded that most young people drink coffee, but juices and soft drinks are consumed more frequently. The coffee selected among young people was those that had the best sensory attributes, soft and strictly soft.